Removal of Binary Mixture of Textile Dyes on Prosopis Juliflora Pods – Equilibrium, Kinetics and Thermodynamics Studies - M. K. Raman; G. Muthuraman (Iranica Journal of Energy and Environment, 2017)
Prosopis juliflora pods is a low cost material obtained from semi-arid region, was evaluated as adsorbent  for the removal of binary textile dye mixture (Gold HE-R and Green HE-4BD).  The effect of pH, concentration of dyes, adsorbent dose and contact time were obtained in batch adsorption technique.  The results were analyzed by isotherm models (Freundlich, Langmuir, Redlich-Peterson and Tempkin).  The results were in good agreement with Langmuir model and the Redlich-Peterson isotherm models. Langmuir monolayer adsorption quantity was found to be, 50.0 mg g-1 and 62.5 mg g-1 for Gold HE-R and Green HE-4BD, respectively.  Pseudo-first-order, pseudo-second-order, intra particle diffusion and Tempkin kinetic models were used to fit the experimental data, it was well fitted into pseudo second order kinetics. Thermodynamic parameters such ∆Ho, ∆So and ∆Go were calculated, which shows the adsorption process was exothermic, decreasing randomness of solute and negative free energy reveals the feasibility of the reaction.  Energy of activation also predicted using Arrhenius equation, which was -16.569 and -20.710 kJ mol-1 for GHER and GHE4BD, respectively.  FT-IR and SEM analysis were also indicates the adsorption pattern effectively.